Analysis of Vocabulary Mastery and Critical Thinking Skills as Preparation for Scientific Presentations: Analisis Penguasaan Kosakata Dan Kemampuan Berpikir Kritis Untuk Bekal Presentasi Ilmiah - Septi Nurhayati (Borneo Educational Journal (Borju), 2023)
The significance of students possessing public speaking skills is an issue that requires attention. As a university student, proficiency in public speaking, in this instance scientific presentations, is unquestionably essential. This is essential if you want to give a presentation, complete an assignment, participate in the community during KKN, etc. Clearly, doing all of this would be a very essential task. In this case, Public Speaking skills in the form of scientific presentations are often used by students, particularly during lectures, from the beginning to the final assignment that must be completed is the skill of presenting a scientific work. In almost all courses, students are frequently required to write and present scientific papers. Presentation is a form of communication that facilitates logical, precise, and persuasive thought. This study seeks to determine the direct relationship between vocabulary mastery and critical thinking skills and students' abilities to present scientific work. This research method is qualitative description, which provides explanations in the form of descriptions based on data from a variety of scientific sources. Using this methodology, researchers are able to explain in detail and in an organized manner the impact of vocabulary mastery and critical thinking skills on students' capacity to present scientific work. Based on the collection, analysis, and research of scientific data and references. The current research will investigate the relationship between vocabulary mastery and critical thinking skills, as well as the impact of these two factors on students' abilities to create scientific presentations